On Software Quality-motivated Design of a Real-time Framework for Complex Robot Control Systems - Reichardt, Max; Föhst, Tobias; Berns, Karsten (Electronic Communications of the EASST, 2013)
Frameworks have fundamental impact on software quality of robot control systems. We propose systematic framework design aiming at high levels of support for all quality attributes that are relevant in the robotics domain. Design decisions are taken accordingly. We argue that certain areas of design are especially critical, as changing decisions there would likely require rewriting significant parts of the implementation. For these areas, quality-motivated solutions and benefits for actual applications are discussed. We illustrate and evaluate their implementations in our framework Finroc - after briefly introducing it. This includes a highly modular framework core and a well-performing, lock-free, zero-copying communication mechanism. Finroc is being used in complex and also in commercial robotic projects - which evinces that the approaches are suitable for real-world applications.